Roles of anti-Müllerian hormone and its duplicates in sex determination and germ cell proliferation of Nile tilapia. Issue 3 (28th December 2021) - Liu, Xingyong; Dai, Shengfei; Wu, Jiahong; Wei, Xueyan; Zhou, Xin; Chen, Mimi; Tan, Dejie; Pu, Deyong; Li, Minghui; Wang, Deshou
Abstract: Duplicates of amh are crucial for fish sex determination and differentiation. In Nile tilapia, unlike in other teleosts, amh is located on X chromosome. The Y chromosome amh ( amh Δ -y ) is mutated with 5 bp insertion and 233 bp deletion in the coding sequence, and tandem duplicate of amh on Y chromosome ( amhy ) has been identified as the sex determiner. However, the expression of amh, amh Δ -y, and amhy, their roles in germ cell proliferation and the molecular mechanism of how amhy determines sex is still unclear. In this study, expression and functions of each duplicate were analyzed. Sex reversal occurred only when amhy was mutated as revealed by single, double, and triple mutation of the 3 duplicates in XY fish. Homozygous mutation of amhy in YY fish also resulted in sex reversal. Earlier and higher expression of amhy /Amhy was observed in XY gonads compared with amh /Amh during sex determination. Amhy could inhibit the transcription of cyp19a1a through Amhr2/Smads signaling. Loss of cyp19a1a rescued the sex reversal phenotype in XY fish with amhy mutation. Interestingly, mutation of both amh and amhy in XY fish or homozygous mutation of amhy in YY fish resulted in infertile females with significantly increased germ cell proliferation. Taken together, these results indicated that up-regulation of amhy during the critical period of sex determination makes it the sex-determining gene, and it functions through repressing cyp19a1a expression via Amhr2/Smads signaling pathway. Amh retained its function in controlling germ cell proliferation as reported in other teleosts, while amh Δ -y was nonfunctionalized.